`y=x^(x^2)`

Before differentiating with respect to x, express this as a logarithmic equation. To do so, take the logarithm of both sides.

`lny=lnx^(x^2)`

At the right side, apply the property `lna^m=mlna` .

`lny=x^2lnx`

Then, differentiate both sides with respect to x.

`d/(dx)lny=d/(dx)(x^2 lnx)`

At the left side, apply the rule `(lnu)'=1/u*u'` .

`1/y* (dy)/(dx)=d/(dx)(x^2 lnx)`

And at the right side apply, the product rule `(u*v)=u*v'+v*u'` .

`1/y* (dy)/(dx)=x^2(lnx)'+lnx(x^2)`

`1/y* (dy)/(dx)=x^2*1/x+lnx*(2x)`

`1/y* (dy)/(dx)=x+2xlnx`

`1/y* (dy)/(dx)=x(1+2lnx)`

Then, isolate dy/dx.

`dy/dx=x(1+2lnx)*y`

Since `y=x^(x^2)` , plug-in this to dy/dx.

`dy/dx=x(1+2lnx)*x^(x^2)`

`dy/dx=x^(x^2+1)(1+2lnx)`

**Hence, `dy/dx=x^(x^2+1)(1+2lnx)` .**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now